2010
DOI: 10.1017/s1047951110000764
|View full text |Cite
|
Sign up to set email alerts
|

Interest of β-blockers in patients with right ventricular systemic dysfunction

Abstract: In patients with cardiac failure due to systemic right ventricular dysfunction, β-blockers improve New York Heart Association class, quality of life, and systemic right ventricular ejection fraction assessed by radionuclide ventriculography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 20 publications
0
27
1
Order By: Relevance
“…Positive RV remodeling 47 vs neutral or possible worsening function, 48 improved exercise duration, 47 improved NYHA functional class 49, 50 and QOL, 50 protective against appropriate shocks 41 …”
Section: Figmentioning
confidence: 99%
“…Positive RV remodeling 47 vs neutral or possible worsening function, 48 improved exercise duration, 47 improved NYHA functional class 49, 50 and QOL, 50 protective against appropriate shocks 41 …”
Section: Figmentioning
confidence: 99%
“…BOUALLAL et al [22] demonstrated the beneficial effects of β-blockers in RV dysfunction, with improvement of RV ejection fraction and NYHA class. However, the patients in that study had RV dysfunction secondary to congenital heart diseases.…”
Section: Figurementioning
confidence: 99%
“…Although there are no randomized control trials in this patient population, evidence based therapies in heart failure with reduced ejection fraction have been applied, which include angiotensin converting enzyme inhibitor or angiotensin II receptor blocker and beta-blocker therapies [14][15][16][17][18][19]. There is no evidence for digoxin; however, it can be used.…”
Section: Medical and Device Therapymentioning
confidence: 99%